Adalimumab in Vogt-Koyanagi-Harada Disease Refractory to Conventional Therapy - Yang, Shizhao; Tao, Tianyu; Huang, Zhaohao; Liu, Xiuxing; Li, He; Xie, Lihui; Wen, Feng; Chi, Wei; Su, Wenru (Frontiers in Medicine, 2022)
Backgroud: No study explores the effectiveness of adalimumab in sight-threatening Vogt-Koyanagi-Harada (VKH) patients in China. Objective: To evaluate the short-term effectiveness and safety of adalimumab (ADA) in patients with sight-threatening Vogt-Koyanagi-Harada (VKH) disease refractory to conventional therapy. Methods: Medical records of VKH patients who had been treated with systemic glucocorticoids and immunosuppressants but whose condition was poorly controlled were collected and analyzed. Primary outcomes comprised of best-corrected visual acuity (BCVA), intraocular inflammation, relapses, and glucocorticoid-sparing effects. Other outcomes included central macular thickness (CMT), intraocular manifestations and adverse events (AEs). Results: Nine refractory VKH patients with a median age of 30 (16, 43) years old were enrolled in this study and received treatment for a median of 10 (7, 11) months. Mean BCVA improved from LogMar 0.63±0.50 (20/72 or 0.36±0.26 in Snellen chart) at baseline to LogMar 0.50±0.37 (20/82 or 0.41±0.28 in Snellen chart) at final visit (P=0.090). The anterior chamber cell grade decreased from 2 (1.75, 3)+ at baseline to 0.5 (0, 1.25)+ cell at final visit (P<0.001). The vitritis grade decreased from 1 (1, 1) + cell at baseline to 0 (0, 1)+ cell at final visit (P<0.001). Patients suffered a median of 1 (0, 2) relapse during treatment. CMT remained stable from 238.50±144.94 μm at baseline to 219.28±77.20 μm at final visit (P=0.553). The mean prednisone dosage decreased from 21.91±18.39 mg/d to 2.73±4.10 mg/d (P=0.005). No severe AEs were found during treatment. Conclusions: The outcomes indicated that ADA was an effective and safe option for VKH patients refractory to conventional therapy by controlling inflammation, preserving visual function and reducing the daily glucocorticoid dose.